2021
DOI: 10.1177/17588359211035710
|View full text |Cite
|
Sign up to set email alerts
|

First- or second-generation epidermal growth factor receptor tyrosine kinase inhibitors in a large, real-world cohort of patients with non-small cell lung cancer

Abstract: Background: There are limited comparisons of first- and second-generation EGFR tyrosine kinase inhibitors (TKIs) in large, real-world cohorts of non-small cell lung cancer (NSCLC) patients with epidermal growth factor receptor ( EGFR) mutations. Methods: Patients with advanced NSCLC ( N = 612) with common EGFR mutations receiving first-line gefitinib/erlotinib and afatinib were grouped and propensity-score matched. Progression-free survival (PFS), overall survival (OS) and secondary T790M mutations were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…In the analysis of previous large cohort studies, the acquired EGFR-T790M mutation rate was higher in NSCLC patients taking first-generation EGFR-TKIs (gefitinib and erlotinib) than in those taking the second-generation EGFR-TKI afatinib. 42 , 43 The secondary EGFR-T790M mutation rates in our study were similar to those in previous cohort studies, and our results indicated that the addition of bevacizumab to first- and second-generation EGFR-TKIs did not affect the frequency or the trend of acquired EGFR-T790M mutation after disease progression.…”
Section: Discussionsupporting
confidence: 89%
“…In the analysis of previous large cohort studies, the acquired EGFR-T790M mutation rate was higher in NSCLC patients taking first-generation EGFR-TKIs (gefitinib and erlotinib) than in those taking the second-generation EGFR-TKI afatinib. 42 , 43 The secondary EGFR-T790M mutation rates in our study were similar to those in previous cohort studies, and our results indicated that the addition of bevacizumab to first- and second-generation EGFR-TKIs did not affect the frequency or the trend of acquired EGFR-T790M mutation after disease progression.…”
Section: Discussionsupporting
confidence: 89%
“…[34][35][36] Older age, poor performance status, and CNS metastasis are known unfavorable clinical factors associated with survival and outcome in advanced EGFR-mutated patients. 37,38 Among the patients with unknown T790M status in our study, 62 patients still received osimertinib (n = 25) and other 3G EGFR-TKIs (n = 37). Chemotherapy is currently recommended as second-line therapy for EGFRmutated patients without secondary T790M after 1G/2G EGFR-TKI therapy because the genetic alterations in T790M-negative patients are heterogeneous and resistant to osimertinib or other 3G EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 98%
“…In Taiwan, 1G/2G EGFR-TKIs, gefitinib, erlotinib, and afatinib are all commonly prescribed as frontline therapy for EGFR-mutated NSCLC patients [ 22 , 23 ]. Although a previous study reported that frontline EGFR-TKIs (gefitinib, erlotinib, and afatinib) had a statistically significant difference in the T790M mutation rate (59.9%, 45.5%, and 52.7%, respectively; p = 0.037) [ 24 ], there was no significant difference in the T790M mutation rate after frontline treatment with different EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 99%